(untitled) (American Journal of Islam and Society, 2014)
In pursuit of a capitalist world configuration, the causal phenomenon of globalization spread its cultural values in the built international system, as evidenced by the dichotomy between the rich North and the poor South. This era of cultural globalization is predominantly characterized by social inequality, economic inequality and instability, political instability, social injustice, and environmental change. Consequently, the world is empirically infected by divergent global inequalities among nations and people, as evidenced by the numerous problems plaguing humanity. This article seeks to understand Islam from the viewpoint of technological determinism in attempt to offset these diverging global inequalities for its “sociopolitical economy”1existence, as well as the stabilization of the interconnected world. Based upon the unifying view of microIslamics, the meaning of Islam and its globalizing perspectives are deciphered on a built micro-religious platform. Finally, the world is rebuilt via the Open World Peace (OWP) paradigm, from which the fluidity of open globalization is derived as a future causal phenomenon for seamlessly bridging (or contracting) the gaps between the rich-rich, rich-poor, poor-rich and poor-poor nations and people based on common civilization fronts.